Evaluation of ultra wideband body area network - Ruckveratham, Bundit; Teawehim, Sanit; Chiochan, Poramade; Promwong, Sathaporn (My University, 2011)
An ultra wideband body area network (UWB-BAN) system can be extremely distorted through a channel even for free-space transmission because of antenna dispersion. Therefore, the understand of antenna characteristics, which effects on waveform distortion, is necessary. This paper presents the waveform distortion due to human body for wireless meadical applications based on measurement data. The template waveform is considered at the receiver side to maximize the SNR for evaluation. In this results are evaluate based on the extended Friis' transmission formula. This technique gives very accurate results and is very useful for the design and evaluation of UWB-BAN transmission waveform for wireless medical applications, especially focusing on the effect of template waveform. © 2011 IEEE.